1991
DOI: 10.1038/350434a0
|View full text |Cite
|
Sign up to set email alerts
|

A pseudoknot-like structure required for efficient self-cleavage of hepatitis delta virus RNA

Abstract: Hepatitis delta virus genomic and antigenomic RNAs contain a self-cleavage site hypothesized to function in processing the viral RNA during replication. Self-cleavage requires only a divalent cation and is mediated at the genomic site by a sequence of less than 85 nucleotides. We propose that the genomic self-cleaving sequence element and a corresponding sequence from the anti-genomic RNA could generate related secondary structures. The region of the antigenomic sequence, predicted from the proposed structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
325
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(336 citation statements)
references
References 14 publications
10
325
0
1
Order By: Relevance
“…In discriminating among the three proposed models regarding to the secondary structure of HDV RNA we found that the axehead model [4] which contains 11 G-C pairs, one A-U pair, and two G-U pairs (based on our sequence) does not agree with the present NMR results. whilst both the pseudoknot model [3] (Fig. l), which contains 15 G-C pairs and two A-U pairs, and the clover leaf model [2], which contains 13 G-C pairs and 2 A-U pairs, are consistent with our NMR data.…”
Section: Assignnzerzt Of the Tetru-loop Inziizo Proton Reso-supporting
confidence: 80%
See 1 more Smart Citation
“…In discriminating among the three proposed models regarding to the secondary structure of HDV RNA we found that the axehead model [4] which contains 11 G-C pairs, one A-U pair, and two G-U pairs (based on our sequence) does not agree with the present NMR results. whilst both the pseudoknot model [3] (Fig. l), which contains 15 G-C pairs and two A-U pairs, and the clover leaf model [2], which contains 13 G-C pairs and 2 A-U pairs, are consistent with our NMR data.…”
Section: Assignnzerzt Of the Tetru-loop Inziizo Proton Reso-supporting
confidence: 80%
“…yielding a 3' cleavage product with a 5' hydroxyl group and a 5' cleavage product with a 9'3'-cyclic phosphoryl group [2]. Several secondary structures have been proposed for genomic HDV RNA, including pseudoknot [3] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The three terminal G residues of the T7 promoter were omitted during construction of the minireplicon to provide a transcriptional start site which began with the precise 5Ј nucleotide of the MUV genome. Inclusion of the HDV ribozyme in the minireplicon construct permitted cleavage of the T7 RNA polymerase transcript to produce the authentic MUV specific 3Ј end (30). The total number of nucleotides (966) in the MUVCAT minireplicon RNA was divisible by 6, in agreement with the "rule of six" proposed for Sendai virus, where it has been suggested that each NP molecule interacts with six nucleotides along the RNA genome, and so genome lengths containing multiples of six nucleotides would be more efficient in replication and rescue (4,22).…”
Section: Resultsmentioning
confidence: 99%
“…CATTCGTCTCTTTTCCAGGTAGTGTCAAAATGCC for addition of the ribozyme component, which is shown in smaller print (30). The CAT ORF cDNA was amplified using primers 5ЈATCATTCGTCTCGGAAAATGGAGAAAAA AATCACTGGATATACC and 5ЈATCATTCGTCTCTCGATTTACGCCCCG CCCTGCCACTC.…”
Section: Cgaggaggctgggaccatgccggccaccaaggggagaatgaatatggg-5јatmentioning
confidence: 99%
“…12,[73][74][75] Consistent with this regulatory model, flanking sequences originated from virus and vector have been shown to affect the HDV ribozyme selfcleaving activity. 71,76 The upstream sequence 5 0 to the self-cleavage site could thus be involved in regulating the selfcleavage activity of the HDV ribozyme when the self-cleavage activity is not desired, but the downstream attenuator not readily available. That is, alternative structures formed co-transcriptionally and being mutually exclusive to the active conformation could potentially temporarily adjust the HDV ribozyme activity.…”
Section: Hdv Ribozymementioning
confidence: 99%